Evaluation for additional work of waterproofing on the retaining wall and capping beam - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding the evaluation for additional work of waterprooﬁng on the retaining wall and capping beam of BRACU new campus project site.